2015
DOI: 10.1590/1807-1929/agriambi.v19n8p719-726
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem das perdas de água por evaporação e arraste de sprays de placa oscilante

Abstract: R E S U M ODentre os diversos fatores que influenciam as perdas de água por evaporação e arraste (PEA) destaca-se o vento. Sendo assim, os objetivos deste trabalho foram: i) determinar os valores de PEA decorrentes de onze avaliações de um sistema de irrigação do tipo pivô central; ii) gerar um modelo para estimativa de PEA a partir de variáveis explicativas; iii) avaliar modelos de predição disponíveis na literatura para estimar PEA a partir de ensaios de campo. Os ensaios foram realizados ao longo de um vão … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(32 reference statements)
0
4
0
1
Order By: Relevance
“…Several studies have been conducted in different Engenharia Agrícola, Jaboticabal, v.40, n.1, p.24-33, jan./feb. 2020 regions of the world with the purpose of modeling or evaluating some existing models for WDEL estimation in sprinkler irrigation systems (Colombo et al, 2015;Faria et al, 2012;Stambouli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted in different Engenharia Agrícola, Jaboticabal, v.40, n.1, p.24-33, jan./feb. 2020 regions of the world with the purpose of modeling or evaluating some existing models for WDEL estimation in sprinkler irrigation systems (Colombo et al, 2015;Faria et al, 2012;Stambouli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…According to Colombo et al (2015), knowledge of the performance of an irrigation system, especially regarding the uniformity of distribution of the applied water depth, is essential for making decisions that allow the rational use of water, energy, and fertilizers. Thus, knowing the influence of weather variables is essential to predict or estimate irrigation uniformity, and even to identify the best time for the operation of a sprinkler irrigation system.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers' findings provide evidence that the scale of wind drift depends on wind speed and weather conditions [117,118] and it varies from 3.6 to 7.2% [119]. Colombo et al reported 3.38% losses of wind drift under the regular operation of CPS [120]. The variation in wind drift was examined by Playan et al in a number of experiments (52 in 2004 and 39 in 2005) and reported the range of the magnitude of losses as 4.3-14.7 in 2004 and 0.3-8.3% in 2005 [121].…”
Section: Sprinkler Design For Better Microclimate and Associated Fiel...mentioning
confidence: 95%
“…Many studies have shown that meteorological conditions have a significant influence on WDELs. Thus, many empirical models have been developed to estimate WDELs by using wind speed as a single variable [22][23][24]28,[33][34][35], and several models have included wind speed and other meteorological variables, such as temperature [13,23,27], relative humidity [23] and vapor pressure deficit [21,36] as parameters. Theoretical models have also been built to incorporate droplet ballistics dynamics and evaporation [37,38].…”
Section: Introductionmentioning
confidence: 99%